2020
DOI: 10.2147/ott.s245134
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-Cancer Activity of Acriflavine as Metabolic Inhibitor of OXPHOS in Pancreas Cancer Xenografts</p>

Abstract: Purpose: All currently available therapies for the treatment of pancreatic ductal adenocarcinoma (PDAC) show limited success. PDACs fast progression depends on the tumor characteristics and can be influenced by the microenvironment. The antibacterial drug acriflavine (ACF) has been shown to have anti-cancer activities in cell lines. Materials and Methods: To understand the working mechanism of ACF on cancer progression and tumor-stromal interplay, we evaluated pancreatic cancer in cell culture (Panc-1) (morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
(59 reference statements)
1
18
0
Order By: Relevance
“…Similarly, FAO inhibitors are developed to achieve the phenotypic transition of macrophages and inhibit tumor development. Furthermore, researchers have revealed that acriflavine (ACF), a heteroaromatic dye with an antibacterial and antiviral effect, shifted macrophage polarization to an M1-like anti-tumoral phenotype by blocking the HIF-1α pathway and enhancing glucose uptake in PDAC ( 94 ). This phenomenon shows that increasing the glucose utilization of TAMs may be a promising direction.…”
Section: Target Glucose Metabolism In Macrophage For Cancer Therapymentioning
confidence: 99%
“…Similarly, FAO inhibitors are developed to achieve the phenotypic transition of macrophages and inhibit tumor development. Furthermore, researchers have revealed that acriflavine (ACF), a heteroaromatic dye with an antibacterial and antiviral effect, shifted macrophage polarization to an M1-like anti-tumoral phenotype by blocking the HIF-1α pathway and enhancing glucose uptake in PDAC ( 94 ). This phenomenon shows that increasing the glucose utilization of TAMs may be a promising direction.…”
Section: Target Glucose Metabolism In Macrophage For Cancer Therapymentioning
confidence: 99%
“…Acriflavine (ACF) is a mixture of 3, 6-diamino-10methyl acridine (trypaflavine) and 3, 6-diamino-acridine (proflavine), which has been used as a preservative and wound healing agent [6]. It has been revealed that ACF can inhibit many cancers, including osteosarcoma, breast cancer, brain cancer, lung cancer, liver cancer, and pancreatic cancer [7][8][9][10][11]. ACF can also act on AIDS patients as an antiviral drug without major side effects [12].…”
Section: Introductionmentioning
confidence: 99%
“…Acriflavine is also known for its fluorescent nature in confocal laser scanning microscopy studies [ 14 ]. It can also be used to inhibit vascularization, tumor growth factors, and HIF-I dimerization [ 15 , 16 ]. It can be used against E-coli and drug-resistant staphylococcus aureus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%